Oil well cement retarder
By using sulfonic acid polymer monomers and carboxylic acid polymer monomers in the cement retarder of oil wells, and adding organic phosphonates and polycarboxylates, the problem of insufficient salt resistance of the existing retarder is solved, and good retarding effect under high temperature and high salt conditions and significant improvement in cement stone strength is achieved.
Patent Information
- Application Number
- CN202311242500.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-03-25
AI Technical Summary
The existing temperature and salt-resistant retarders in cementing cement slurry have insufficient salt resistance, which affects the development of cement stone strength.
The polymer formed by sulfonic acid polymer monomer and carboxylic acid polymer monomer is used, and organic phosphonates and polycarboxylate are combined as salt additives to adjust the performance of the retarder.
It improves the salt resistance and retarding effect of the retarder, performs well under wide temperate conditions, is highly adaptable, and is not sensitive to saline concentration, which can effectively improve the early strength growth of cement stone.
Smart Images

Figure CN119684982A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an oil well cement retarder, belonging to the technical field of oil well cement admixtures. Background Art
[0002] Cementing of oil and gas wells is to inject cement slurry into the casing and wellbore annulus. After the cement slurry solidifies, it plays the role of isolating formation fluids, supporting casing and protecting production layers. Cementing is an important part of oil and gas well construction, and the quality of cementing determines the life of oil and gas wells. During the construction process, the cementing cement slurry must have good fluidity before reaching the target position to ensure the safety of the entire operation process. Therefore, admixtures are usually added to the cementing cement slurry to adjust the various properties of the cement slurry. Retarders, as an important admixture of cementing cement, are mainly used to regulate the gel time of cementing cement slurry to meet the requirements of cementing construction. Commonly used retarders mainly include sodium lignin sulfonate, sugar compounds, organic phosphonic acid and its salts, and hydroxycarboxylates. These retarders have problems such as poor temperature resistance, sensitive dosage, and difficult to control the retarding effect. They are also poorly adaptable to salt-based cementing cement slurry and may even have a counterproductive effect.
[0003] In order to improve the applicability of oil well cement retarders in cementing of different types of oil reservoirs, people have conducted a lot of research. For example, Chinese patent document CN112980409A discloses a retarder suitable for large temperature difference cementing and its preparation method. The retarder is mixed with 10-30% of ethylenediaminetetramethyl sodium phosphate, 10-20% of borax and 60-70% of ternary polymer, which can meet the retarding requirements of cement slurry in the entire temperature range of 50°C and 180°C at the upper and lower ends of the cement slurry section in cementing construction, and can ensure that the cement slurry has a certain strength under the high temperature and large temperature difference environment of 50°C at the top, avoiding the "super retarding phenomenon" of the top cement. However, although this type of retarder is weakly sensitive to temperature, its applicability with salt water-based cement slurry cannot meet the requirements. Chinese patent document CN114891145A provides a four-element copolymer type heat-resistant and salt-resistant retarder formed by copolymerization of sodium p-vinylbenzene sulfonate, acrylamide, itaconic acid and dimethyldiallylammonium chloride. This type of retarder has significant retarding performance in the temperature range of 90-240°C, and when the NaCl content of the slurry water is 18%, the thickening curve has good linearity, no abnormalities such as "bulging" and "stepping", and the right-angle thickening effect is obvious. However, this retarder has a great influence on the strength development of cement stone, and the compressive strength of the cement slurry system is only 5.6MPa, which cannot guarantee the cementing quality. Summary of the invention
[0004] The object of the present invention is to provide an oil well cement retarder, which can solve the problem that the strength development of cement paste is affected due to insufficient salt resistance when the current temperature-resistant and salt-resistant retarders are used in cementing cement slurry.
[0005] In order to achieve the above purpose, the technical solution adopted by the oil well cement retarder of the present invention is:
[0006] An oil well cement retarder comprises a polymer and a salt additive; the salt additive comprises an organic phosphonate and a polycarboxylate, and the mass ratio of the organic phosphonate to the polycarboxylate is (1-3):(0.5-1); the polymer is prepared by a method comprising the following steps: subjecting a polymerizing monomer to a polymerization reaction in a solvent under the action of an initiator; the polymerizing monomer comprises a sulfonic acid polymerizing monomer and a carboxylic acid polymerizing monomer, and the mass ratio of the sulfonic acid polymerizing monomer to the carboxylic acid polymerizing monomer is (8-9):(1-2); the structural formula of the sulfonic acid polymerizing monomer is: MRN, where M is an acrylamide group or a methacrylamide group, R is an alkylene group, and N is a sulfonic acid group or a sulfonate group; the carboxylic acid polymerizing monomer has two or more functional groups and one or more ethylenically unsaturated double bonds, and the functional group is a carboxyl group or a carboxylate group.
[0007] The oil well cement retarder of the present invention contains a polymer formed by a sulfonic acid polymerized monomer and a carboxylic acid polymerized monomer, and contains organic phosphonates and polycarboxylates at the same time, which can work together to improve the retarding effect and salt resistance; the carboxylic acid group in the polymer can be complexed with calcium ions on the surface of cement particles to form a polymer film on the surface of cement particles to inhibit the hydration of cement particles; organic phosphonates and polycarboxylates can help improve the retarding effect and improve the dispersibility of cement particles. The oil well cement retarder of the present invention has a good retarding effect under wide temperate conditions, has strong adaptability to brine cement slurry, is insensitive to brine concentration, does not cause abnormal thickening curves in brine-based cementing cement slurry under high temperature conditions, and has an obvious linear relationship between the amount of retarder added and the thickening time, and the thickening transition time is short. At the same time, because the polycarboxylate has a relatively long molecular side chain, the adsorption state of the copolymer molecule on the surface of cement stone particles is improved, and the formation of fine calcium vanadium crystals is promoted, which can effectively improve the growth of the early strength of cement stone and can better meet the needs of cementing operations.
[0008] When the amount of polymer is too much, the cement slurry will be unstable when the retarder is used above 120°C, and the thickening curve will show "bulges", "steps" and long transition time. When the amount of salt additives is too much, the polymer molecular chain in the retarder will curl up, resulting in a decrease in the polymer retarding effect. At the same time, the linear relationship between the amount of retarder added and the thickening time will not be obvious, which is not conducive to the safety of cementing construction and it is difficult to ensure the quality of cementing.
[0009] The monomer ratio is the main factor affecting the retarding properties of the copolymer. When the ratio of sulfonic acid monomers to carboxylic acid monomers in the polymerization monomers is too high, the synthesized polymer has a larger relative molecular mass, a longer molecular chain, and is prone to curling. Some carboxylic acid groups are wrapped inside, which will limit the chelating and dispersing effect of the polymer, thereby reducing the retarding effect.
[0010] If salt additives (including organic phosphonates and polycarboxylates) are mixed and reacted with polymer monomers under the action of an initiator at a polymerization temperature, the copolymer monomers cannot fully react under the action of the initiator and the retarding effect of the copolymer cannot be effectively exerted.
[0011] Preferably, the total mass of the polymerized monomers used in preparing the polymer is P, and the mass of the salt additive is O, then P:O=20:(1-4).
[0012] In order to ensure that the prepared polymer can be used directly without removing the solvent, preferably, the solvent is water.
[0013] In order to ensure that the polymerization monomer can react stably in water and maintain a high reaction rate, preferably, the mass ratio of the sulfonic acid polymerization monomer, the carboxylic acid polymerization monomer and water is (16-18): (2-4): (80-100). For example, the mass ratio of the sulfonic acid polymerization monomer, the carboxylic acid polymerization monomer and water is (8-9): (1-2): 80.
[0014] Preferably, R is propylene, butylene, or pentylene. For example, R is n-propylene, isopropylene, n-butylene, isobutylene, or sec-butylene. When R is isobutylene, the sulfonic acid polymerizable monomer is 2-acrylamide-2-methylpropane sulfonic acid and / or 2-acrylamide-2-methylpropane sulfonate. For example, the sulfonic acid polymerizable monomer is 2-acrylamide-2-methylpropane sulfonic acid or water-soluble 2-acrylamide-2-methylpropane sulfonate. For example, the water-soluble 2-acrylamide-2-methylpropane sulfonate is an alkali metal salt of 2-acrylamide-2-methylpropane sulfonic acid.
[0015] Preferably, the carboxylic acid polymerizable monomer is selected from one or any combination of itaconic acid, itaconic acid monocarboxylate, itaconic acid dicarboxylate, 2-methyleneglutaric acid, 2-methyleneglutaric acid monocarboxylate, and 2-methyleneglutaric acid dicarboxylate. For example, the carboxylic acid polymerizable monomer is selected from one or any combination of itaconic acid, itaconic acid monocarboxylate alkali metal salt, itaconic acid dicarboxylate alkali metal salt, 2-methyleneglutaric acid, 2-methyleneglutaric acid monocarboxylate alkali metal salt, and 2-methyleneglutaric acid dicarboxylate alkali metal salt.
[0016] In order to ensure that the polymerization reaction can be carried out at a lower temperature and fully react, preferably, the initiator is selected from one or any combination of persulfate and azo compounds. In order to ensure that the initiator can be soluble in water, preferably, the initiator is a water-soluble initiator. For example, the persulfate is an alkali metal persulfate or ammonium persulfate; the azo compound is azobisisobutylimidazoline hydrochloride.
[0017] In order to ensure that the polymerization reaction is relatively complete and obtain a polymer with a suitable molecular weight, preferably, the mass ratio of the sulfonic acid polymerization monomer, the carboxylic acid polymerization monomer and the initiator is (16-18): (2-4): (0.2-0.5). Preferably, the polymerization reaction temperature is 50-60°C and the time is 4-6h.
[0018] In the present invention, when N is a sulfonate group and the functional group is a carboxylate group, the sulfonic acid polymer monomer and the carboxylic acid polymer monomer can be directly polymerized in water under the action of an initiator; when N is a sulfonic acid group or the functional group is a carboxyl group, the sulfonic acid polymer monomer and the carboxylic acid polymer monomer can be directly reacted with an alkaline compound to obtain the corresponding sulfonate group or carboxylate group and then polymerized; or the sulfonic acid polymer monomer and the carboxylic acid polymer monomer can be firstly polymerized, and then the product after the polymerization reaction is reacted with an alkaline compound to convert the sulfonic acid group or carboxyl group in the product after the polymerization reaction into a sulfonate group or a carboxylate group.
[0019] Preferably, the N is a sulfonic acid group, the functional group is a carboxyl group, and the polymerization reaction method comprises the following steps: adjusting the pH of a mixture consisting of a polymerization monomer and a solvent to neutral to obtain a mixed solution, then heating the mixed solution to a temperature required for the polymerization reaction, and then adding an initiator to the mixed solution and mixing to carry out the polymerization reaction.
[0020] The pH adjuster used to adjust the pH of the mixture to neutral is an alkaline pH adjuster, which is an alkaline solution or an alkaline compound, for example, a sodium hydroxide solution or sodium hydroxide.
[0021] The phosphonate in the organic phosphonate molecule can form a precipitate with the calcium ions formed by cement hydration, covering the surface of cement particles, playing a role in slowing down cement hydration. In order to better work together with the system after the polymerization reaction, and then form a retarder with better performance, preferably, the organic phosphonate is hydroxy ethylidene diphosphonate and / or alkyl diamine tetra methylene phosphate. For example, the hydroxy ethylidene diphosphonate is disodium hydroxy ethylidene diphosphonate and dipotassium hydroxy ethylidene diphosphonate; the alkyl diamine tetra methylene phosphate is ethylene diamine tetra methylene phosphate and / or hexamethylene diamine tetra methylene phosphate. For example, the alkyl diamine tetra methylene phosphate is sodium ethylene diamine tetra methylene phosphate and potassium ethylene diamine tetra methylene phosphate. Compared with other organic phosphonates (for example, sodium hypophosphite, diethylene triamine penta methylene phosphonic acid, etc.), the beneficial effect of selecting hydroxy ethylidene diphosphonate and / or alkyl diamine tetra methylene phosphate is that they have good applicability in a wide temperate environment.
[0022] Preferably, the polycarboxylate is polyaspartate and / or polyepoxysuccinate. For example, the polycarboxylate is polyaspartic acid alkali metal salt and / or polyepoxysuccinate alkali metal salt. For example, the polycarboxylate is sodium polyaspartate, potassium polyaspartate, sodium polyepoxysuccinate, potassium polyepoxysuccinate. Compared to other polycarboxylates (e.g., sodium polyacrylate, etc.), polyaspartate and / or polyepoxysuccinate have better dispersibility.
[0023] Preferably, the number average molecular weight of the polyaspartate is 2500-5000; the number average molecular weight of the polyepoxysuccinate is 2500-5000.
[0024] For ease of use, preferably, the oil well cement retarder also includes water.
[0025] In order to ensure that the salt additive and the polymer can be mixed evenly, preferably, the oil well cement retarder is prepared by mixing an aqueous dispersion of the polymer and an aqueous dispersion of the salt additive. Preferably, in the aqueous dispersion of the salt additive, the mass ratio of organic phosphonate, polycarboxylate and water is (1-3):(0.5-1):(20-40). For example, in the aqueous dispersion of the salt additive, the mass ratio of organic phosphonate, polycarboxylate and water is (1-3):(0.5-1):20. Preferably, the aqueous dispersion of the polymer is the system after the polymerization reaction.
[0026] In order to ensure that the aqueous dispersion of the polymer and the aqueous dispersion of the salt additive can be mixed uniformly, preferably, the mixing temperature of the aqueous dispersion of the polymer and the aqueous dispersion of the salt additive is not less than 50°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1This is a schematic diagram of a thickening curve of the oil well cement retarder of Example 1 of the present invention tested under the conditions of an addition amount of 0.1%, a test temperature of 100° C., and a test pressure of 60.2 MPa;
[0028] Figure 2 It is a schematic diagram of the thickening curve of the oil well cement retarder of Example 2 of the present invention tested under the conditions of an addition amount of 0.3%, a test temperature of 100° C., and a test pressure of 60.2 MPa;
[0029] Figure 3 This is a schematic diagram of the thickening curve of the oil well cement retarder of Example 3 of the present invention tested under the conditions of an addition amount of 0.1%, a test temperature of 60° C., and a test pressure of 32.8 MPa;
[0030] Figure 4 It is a schematic diagram of the thickening curve of the oil well cement retarder of Example 3 of the present invention tested under the conditions of an addition amount of 0.1%, a test temperature of 80° C., and a test pressure of 46.5 MPa;
[0031] Figure 5 It is a schematic diagram of the thickening curve of the oil well cement retarder of Example 3 of the present invention tested under the conditions of an addition amount of 0.5%, a test temperature of 100° C., and a test pressure of 60.2 MPa;
[0032] Figure 6 It is a schematic diagram of the thickening curve of the oil well cement retarder of Example 3 of the present invention tested under the conditions of an addition amount of 0.3%, a test temperature of 120° C., and a test pressure of 73.9 MPa;
[0033] Figure 7 It is a schematic diagram of the thickening curve of the oil well cement retarder of Example 3 of the present invention tested under the conditions of an addition amount of 1.0%, a test temperature of 150° C., and a test pressure of 94.4 MPa;
[0034] Figure 8 It is a schematic diagram of the thickening curve of the oil well cement retarder of Example 4 of the present invention tested under the conditions of an addition amount of 0.2%, a test temperature of 100° C., and a test pressure of 60.2 MPa;
[0035] Fig. 9 This is a schematic diagram of a thickening curve of the oil well cement retarder of Example 5 of the present invention tested under the conditions of an addition amount of 0.2%, a test temperature of 100° C., and a test pressure of 60.2 MPa;
[0036] Fig.10 It is a schematic diagram of the thickening curve of the cementing slurry G1 of the present invention tested at a test temperature of 100° C. and a test pressure of 60.2 MPa;
[0037] Fig.11It is a schematic diagram of the thickening curve of the oil well cement retarder of comparative example 1 of the present invention tested under the conditions of an addition amount of 0.2%, a test temperature of 100° C., and a test pressure of 60.2 MPa. DETAILED DESCRIPTION
[0038] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0039] Example 1
[0040] The oil well cement retarder of the present embodiment is mainly composed of water, polymer and salt additives, and is prepared by a method comprising the following steps:
[0041] (1) adding 18 parts by mass of 2-acrylamido-2-methylpropanesulfonic acid and 2 parts by mass of itaconic acid to 80 parts by mass of deionized water, respectively, and stirring to obtain a polymerization monomer solution, and then adjusting the polymerization monomer solution to neutrality with a sodium hydroxide solution having a mass fraction of 30% to obtain a mixed solution;
[0042] (2) adding 3 parts by weight of disodium hydroxyethylidene diphosphonate and 0.5 parts by weight of sodium polyepoxysuccinate (number average molecular weight of 2500 to 5000) to 20 parts by weight of deionized water, respectively, and stirring until fully dissolved to obtain a salt additive solution;
[0043] (3) The mixed solution prepared in step (1) is heated to 60° C., 0.5 parts by weight of sodium persulfate is added under magnetic stirring conditions, and the mixture is stirred at a constant temperature for 4 hours to obtain an aqueous dispersion of the polymer, and then the salt additive solution is added dropwise to the aqueous dispersion of the polymer. After the addition is completed, stirring is continued for 1 hour to obtain an oil well cement retarder.
[0044] Example 2
[0045] The oil well cement retarder of the present embodiment is mainly composed of water, polymer and salt additives, and is prepared by a method comprising the following steps:
[0046] (1) adding 16 parts by mass of 2-acrylamido-2-methylpropanesulfonic acid and 4 parts by mass of itaconic acid to 80 parts by mass of deionized water, respectively, and stirring to obtain a polymerization monomer solution, and then adjusting the polymerization monomer solution to neutrality with a sodium hydroxide solution having a mass fraction of 30% to obtain a mixed solution;
[0047] (2) adding 3 parts by weight of disodium hydroxyethylidene diphosphonate and 0.5 parts by weight of sodium polyepoxysuccinate (number average molecular weight of 2500 to 5000) to 20 parts by weight of deionized water, respectively, and stirring until fully dissolved to obtain a salt additive solution;
[0048] (3) The mixed solution prepared in step (1) is heated to 60° C., 0.5 parts by weight of sodium persulfate is added under magnetic stirring conditions, and the mixture is stirred at a constant temperature for 4 hours to obtain an aqueous dispersion of the polymer, and then the salt additive solution is added dropwise to the aqueous dispersion of the polymer. After the addition is completed, stirring is continued for 1 hour to obtain an oil well cement retarder.
[0049] Example 3
[0050] The oil well cement retarder of the present embodiment is mainly composed of water, polymer and salt additives, and is prepared by a method comprising the following steps:
[0051] (1) adding 18 parts by mass of 2-acrylamido-2-methylpropanesulfonic acid and 2 parts by mass of itaconic acid to 80 parts by mass of deionized water, respectively, and stirring to obtain a polymerization monomer solution, and then adjusting the polymerization monomer solution to neutrality with a sodium hydroxide solution having a mass fraction of 30% to obtain a mixed solution;
[0052] (2) adding 3 parts by weight of disodium hydroxyethylidene diphosphonate and 0.5 parts by weight of sodium polyaspartate (number average molecular weight of 2500 to 5000) to 20 parts by weight of deionized water, respectively, and stirring until fully dissolved to obtain a salt additive solution;
[0053] (3) The mixed solution prepared in step (1) is heated to 60° C., 0.5 parts by weight of sodium persulfate is added under magnetic stirring conditions, and the mixture is stirred at a constant temperature for 4 hours to obtain an aqueous dispersion of the polymer, and then the salt additive solution is added dropwise to the aqueous dispersion of the polymer. After the addition is completed, stirring is continued for 1 hour to obtain an oil well cement retarder.
[0054] Example 4
[0055] The oil well cement retarder of the present embodiment is mainly composed of water, polymer and salt additives, and is prepared by a method comprising the following steps:
[0056] (1) adding 18 parts by mass of 2-acrylamido-2-methylpropanesulfonic acid and 2 parts by mass of itaconic acid to 80 parts by mass of deionized water, respectively, and stirring to obtain a polymerization monomer solution, and then adjusting the polymerization monomer solution to neutrality with a sodium hydroxide solution having a mass fraction of 30% to obtain a mixed solution;
[0057] (2) adding 3 parts by weight of sodium ethylenediaminetetramethylenephosphate and 1 part by weight of sodium polyaspartate (number average molecular weight of 2500 to 5000) to 20 parts by weight of deionized water, respectively, and stirring until fully dissolved to obtain a salt additive solution;
[0058] (3) The mixed solution prepared in step (1) is heated to 60° C., 0.5 parts by weight of sodium persulfate is added under magnetic stirring conditions, and the mixture is stirred at a constant temperature for 4 hours to obtain an aqueous dispersion of the polymer, and then the salt additive solution is added dropwise to the aqueous dispersion of the polymer. After the addition is completed, stirring is continued for 1 hour to obtain an oil well cement retarder.
[0059] Example 5
[0060] The oil well cement retarder of the present embodiment is mainly composed of water, polymer and salt additives, and is prepared by a method comprising the following steps:
[0061] (1) adding 18 parts by mass of 2-acrylamido-2-methylpropanesulfonic acid and 2 parts by mass of itaconic acid to 80 parts by mass of deionized water, respectively, and stirring to obtain a polymerization monomer solution, and then adjusting the polymerization monomer solution to neutrality with a sodium hydroxide solution having a mass fraction of 30% to obtain a mixed solution;
[0062] (2) adding 1 part by weight of sodium ethylenediaminetetramethylenephosphate and 0.5 part by weight of sodium polyaspartate (number average molecular weight of 2500 to 5000) to 20 parts by weight of deionized water, respectively, and stirring until fully dissolved to obtain a salt additive solution;
[0063] (3) The mixed solution prepared in step (1) is heated to 50° C., 0.5 parts by weight of sodium persulfate is added under magnetic stirring conditions, and the mixture is stirred at a constant temperature for 6 hours to obtain an aqueous dispersion of the polymer, and then the salt additive solution is added dropwise to the aqueous dispersion of the polymer. After the addition is completed, stirring is continued for 1 hour to obtain an oil well cement retarder.
[0064] Comparative Example 1
[0065] The oil well cement retarder of this comparative example is prepared by a method comprising the following steps:
[0066] (1) adding 18 parts by mass of 2-acrylamido-2-methylpropanesulfonic acid and 2 parts by mass of itaconic acid to 100 parts by mass of deionized water, respectively, and stirring to obtain a polymerization monomer solution, and then adjusting the polymerization monomer solution to neutrality with a sodium hydroxide solution having a mass fraction of 30% to obtain a mixed solution;
[0067] (2) The mixed solution prepared in step (1) is heated to 60° C., 0.5 parts by weight of sodium persulfate is added under magnetic stirring, and the mixture is stirred at a constant temperature for 5 hours to obtain an oil well cement retarder.
[0068] Comparative Example 2
[0069] The oil well cement retarder of this comparative example is prepared by a method comprising the following steps:
[0070] 24 parts by mass of sodium ethylenediaminetetramethylenephosphate was added to 100 parts by mass of deionized water, and stirred until fully dissolved to obtain an oil well cement retarder.
[0071] Comparative Example 3
[0072] The only difference between the oil well cement retarder of this comparative example and the oil well cement retarder of Example 1 is that, during the preparation of the oil well cement retarder of this comparative example, the mass fraction of 2-acrylamido-2-methylpropanesulfonic acid in step (1) is adjusted from 18 parts to 18.4 parts, the mass fraction of itaconic acid is adjusted from 2 parts to 2.04 parts, and the mass fraction of disodium hydroxyethylidene diphosphonate in step (2) is adjusted from 3 parts to 3.05 parts, and the mass fraction of sodium polyepoxysuccinate is adjusted from 0.5 parts to 0 parts, and the mass fraction of sodium persulfate in step (3) is adjusted from 0.5 parts to 0.51 parts.
[0073] Comparative Example 4
[0074] The only difference between the oil well cement retarder of this comparative example and the oil well cement retarder of Example 1 is that, during the preparation of the oil well cement retarder of this comparative example, the mass fraction of 2-acrylamido-2-methylpropanesulfonic acid in step (1) is adjusted from 18 parts to 20.5 parts, the mass fraction of itaconic acid is adjusted from 2 parts to 2.3 parts, and the mass fraction of disodium hydroxyethylidene diphosphonate in step (2) is adjusted from 3 parts to 0 parts, and the mass fraction of sodium polyepoxysuccinate is adjusted from 0.5 parts to 0.6 parts, and the mass fraction of sodium persulfate in step (3) is adjusted from 0.5 parts to 0.6 parts.
[0075] Comparative Example 5
[0076] The oil well cement retarder of this comparative example is prepared by a method comprising the following steps: adding 20.6 parts by mass of disodium hydroxyethylidene diphosphonate and 3.4 parts by mass of sodium polyepoxysuccinate to 100 parts by mass of water, stirring evenly until fully dissolved to obtain a salt additive solution, and then heating the salt additive solution to 60° C. and stirring at a constant temperature for 5 hours to obtain the oil well cement retarder.
[0077] Experimental example
[0078] In order to evaluate the use effect of the oil well cement retarders of Examples 1-5 and Comparative Examples 1-5, the performance of each oil well cement retarder was evaluated according to the method specified in Standard 198.SY-T 5504.1-2013 "Evaluation Method for Oil Well Cement Admixtures Part 1: Retarders". During the test, each oil well cement retarder was added to the cementing cement slurry for thickening test and compressive strength test. The thickening test was carried out at a certain temperature and pressure, and the compressive strength test was carried out after the cement slurry was cured at a certain curing temperature and curing pressure (21MPa) for 24 hours.
[0079] When preparing cement slurry, different mass fractions of brine are used for preparation. The amount of each oil well cement retarder (the percentage of the amount of oil well cement retarder added in the cement in the cement slurry), the concentration of the brine used when preparing the cement slurry, and the test results and test conditions corresponding to each oil well cement retarder are shown in Table 1. Among them, the cementing cement slurry G1 used when the test temperature is not more than 120°C is composed of the following components in mass parts: 100 parts of Tongchuan G grade cement, 0.5 parts of dispersant, 1.2 parts of fluid loss agent, 1 part of microsilicon, 0.5 parts of metasilicate + 1 part of toughening agent, and the water-cement ratio is 0.45; the cementing cement slurry G2 used when the test temperature is greater than 120°C is composed of the following components in mass parts: 100 parts of Tongchuan G grade cement, 35 parts of quartz sand, 0.5 parts of dispersant, 1.5 parts of fluid loss agent, 1 part of microsilicon, 0.5 parts of metasilicate, 1 part of toughening agent, and the water-cement ratio is 0.60. The water used in cementing slurry is brine with different mass fractions.
[0080] The thickening curves of cement slurry G1 and various oil well cement retarders tested under different conditions are shown in Figure 2. Figure 1-11 As shown; among them, Figure 1 This is a schematic diagram of a thickening curve of the oil well cement retarder of Example 1 of the present invention tested under the conditions of an addition amount of 0.1%, a test temperature of 100° C., and a test pressure of 60.2 MPa; Figure 2 It is a schematic diagram of the thickening curve of the oil well cement retarder of Example 2 of the present invention tested under the conditions of an addition amount of 0.3%, a test temperature of 100° C., and a test pressure of 60.2 MPa; Figure 3 This is a schematic diagram of the thickening curve of the oil well cement retarder of Example 3 of the present invention tested under the conditions of an addition amount of 0.1%, a test temperature of 60° C., and a test pressure of 32.8 MPa; Figure 4 It is a schematic diagram of the thickening curve of the oil well cement retarder of Example 3 of the present invention tested under the conditions of an addition amount of 0.1%, a test temperature of 80° C., and a test pressure of 46.5 MPa; Figure 5 It is a schematic diagram of the thickening curve of the oil well cement retarder of Example 3 of the present invention tested under the conditions of an addition amount of 0.5%, a test temperature of 100° C., and a test pressure of 60.2 MPa; Figure 6 It is a schematic diagram of the thickening curve of the oil well cement retarder of Example 3 of the present invention tested under the conditions of an addition amount of 0.3%, a test temperature of 120° C., and a test pressure of 73.9 MPa; Figure 7 It is a schematic diagram of the thickening curve of the oil well cement retarder of Example 3 of the present invention tested under the conditions of an addition amount of 1.0%, a test temperature of 150° C., and a test pressure of 94.4 MPa; Figure 8It is a schematic diagram of the thickening curve of the oil well cement retarder of Example 4 of the present invention tested under the conditions of an addition amount of 0.2%, a test temperature of 100° C., and a test pressure of 60.2 MPa; Fig. 9 This is a schematic diagram of a thickening curve of the oil well cement retarder of Example 5 of the present invention tested under the conditions of an addition amount of 0.2%, a test temperature of 100° C., and a test pressure of 60.2 MPa; Fig.10 It is a schematic diagram of the thickening curve of the cementing slurry G1 of the present invention tested at a test temperature of 100° C. and a test pressure of 60.2 MPa; Fig.11 The thickening curve of the oil well cement retarder of comparative example 1 of the present invention is tested under the conditions of 0.2% addition, 100°C test temperature and 60.2MPa test pressure. The thickening time in Table 1 refers to the time taken for the cement slurry to reach a consistency of 100BC after preparation, and the transition time refers to the time taken for the cement slurry to reach a consistency of 100BC from 40BC.
[0081] Table 1 The amount of cement retarders added for each oil well, the concentration of brine used in preparing cement slurry, and the test results corresponding to each oil well cement retarder
[0082]
[0083]
[0084] As shown in Table 1, the oil well cement retarder of the present invention can be well adapted to the cementing slurry system prepared with high concentration brine, and the amount of the oil well cement retarder added and the thickening time show an obvious linear relationship. In addition, the oil well cement retarder of the present invention can react with the Ca in the cement slurry through the groups on different components in the retarder in the temperature range of 60 to 150°C. 2+ The effective adsorption degree between the two can effectively adjust the thickening time of salt water-based cementing slurry, and the thickening transition time is short, which is much less than the 40 minutes specified in the standard. The 24h compressive strength of the cement slurry prepared by the oil well cement retarder of the present invention is significantly higher than the 14MPa specified in the standard, which can well meet the requirements of cementing operations.
[0085] After replacing the sodium persulfate in Example 1 with ammonium persulfate, potassium persulfate or azobis(isobutylene)imidazoline hydrochloride, the performance of the obtained oil well cement retarder was evaluated according to the method of the experimental example. The results showed that the performance of the obtained oil well cement retarder was consistent with that of the oil well cement retarder in Example 1.
[0086] In addition, the mass fraction of deionized water in step (1) of Example 1 is replaced by 80 parts to 100 parts, or the mass fraction of deionized water in step (2) of Example 1 is replaced by 20 parts to 40 parts, or the mass fraction of sodium persulfate in step (3) of Example 1 is replaced by 0.5 parts to 0.2 parts, or the time for continuing the stirring reaction in step (3) of Example 1 is replaced by 1 hour to 2 hours, or the disodium of hydroxyethylidene diphosphonic acid in step (2) is replaced by dipotassium of hydroxyethylidene diphosphonic acid, or the sodium polyepoxysuccinate in step (2) is replaced by potassium polyepoxysuccinate, or the step (1) is replaced by potassium polyepoxysuccinate. In the step (1), the 2-acrylamido-2-methylpropanesulfonic acid is replaced by sodium 2-acrylamido-2-methylpropanesulfonate or potassium 2-acrylamido-2-methylpropanesulfonate, or the itaconic acid in step (1) is replaced by 2-methyleneglutaric acid, monosodium itaconate, disodium itaconate, monopotassium itaconate, dipotassium itaconate, monosodium 2-methyleneglutaric acid, disodium 2-methyleneglutaric acid, monopotassium 2-methyleneglutaric acid, or dipotassium 2-methyleneglutaric acid. When the performance of the obtained oil well cement retarder is evaluated according to the method of the experimental example, it is found that the performance of the obtained oil well cement retarder is consistent with that of the oil well cement retarder of Example 1.
[0087] Finally, after replacing the sodium ethylenediaminetetramethylenephosphate in step (2) of Example 4 with sodium hexamethylenediaminetetramethylenephosphate and potassium hexamethylenediaminetetramethylenephosphate, the performance of the obtained oil well cement retarder was evaluated according to the method of the experimental example. The results showed that the performance of the obtained oil well cement retarder was consistent with that of the oil well cement retarder of Example 4.
Claims
1. An oil well cement retarder, characterized in that: The invention comprises a polymer and a salt additive; the salt additive comprises an organic phosphonate and a polycarboxylate, and the mass ratio of the organic phosphonate to the polycarboxylate is (1-3):(0.5-1); the polymer is prepared by a method comprising the following steps: subjecting a polymerizing monomer to a polymerization reaction in a solvent under the action of an initiator; the polymerizing monomer comprises a sulfonic acid polymerizing monomer and a carboxylic acid polymerizing monomer, and the mass ratio of the sulfonic acid polymerizing monomer to the carboxylic acid polymerizing monomer is (8-9):(1-2); the structural formula of the sulfonic acid polymerizing monomer is: MRN, where M is an acrylamide group or a methacrylamide group, R is an alkylene group, and N is a sulfonic acid group or a sulfonate group; the carboxylic acid polymerizing monomer has two or more functional groups and one or more ethylenically unsaturated double bonds, and the functional group is a carboxyl group or a carboxylate group.
2. The oil well cement retarder according to claim 1, characterized in that: R is propylene, butylene or pentylene.
3. The oil well cement retarder according to claim 2, characterized in that: R is n-propylene, isopropylene, n-butylene, isobutylene, or sec-butylene.
4. The oil well cement retarder according to claim 1, characterized in that: The carboxylic acid polymer monomer is selected from one or any combination of itaconic acid, itaconic acid monocarboxylate, itaconic acid dicarboxylate, 2-methyleneglutaric acid, 2-methyleneglutaric acid monocarboxylate, and 2-methyleneglutaric acid dicarboxylate.
5. The oil well cement retarder according to any one of claims 1 to 4, characterized in that: The organic phosphonate is hydroxyethylidene diphosphonate and / or alkyl diamine tetramethylene phosphate.
6. The oil well cement retarder according to claim 5, characterized in that: The hydroxyethylidene diphosphonate is disodium hydroxyethylidene diphosphonate or dipotassium hydroxyethylidene diphosphonate; the alkyldiaminetetramethylene phosphate is ethylenediaminetetramethylene phosphate and / or hexamethylenediaminetetramethylene phosphate.
7. The oil well cement retarder according to any one of claims 1 to 4, characterized in that: The polycarboxylate is polyaspartate and / or polyepoxysuccinate.
8. The oil well cement retarder according to claim 7, characterized in that: The number average molecular weight of the polyaspartate is 2500-5000; the number average molecular weight of the polyepoxysuccinate is 2500-5000.
9. The oil well cement retarder according to claim 7, characterized in that: The polycarboxylate is an alkali metal salt of polyaspartic acid and / or an alkali metal salt of polyepoxysuccinic acid.
10. The oil well cement retarder according to any one of claims 1 to 4, characterized in that: The initiator is selected from one or any combination of persulfate and azo compounds; the polymerization reaction temperature is 50-60° C. and the time is 4-6 hours; the total mass of the polymerization monomers used in preparing the polymer is P, the mass of the salt additive is O, and then P:O=20:(1-4).
Citation Information
Patent Citations
Retarder suitable for large-temperature-difference well cementation and preparation method thereof
CN112980409A
Temperature-resistant and salt-resistant retarder for well cementation as well as preparation method and application of temperature-resistant and salt-resistant retarder
CN114891145A
Oil well cement inhibiting agent
CN101368091A
Medium-high-temperature oil well cement retarding agent as well as preparation method and application thereof
CN109503760A
Preparation method of retarder for water reducing agent
CN114853381A